Extending the shelf life of fresh durian (Durio zibethinus) - Mohamed, Suhaila (Universiti Putra Malaysia Press, 1990)
Ripe durians collected after they have fallen to the ground undergo dehiscence within 3 days of ripening. In a preliminary study to investigate methods of preventing dehiscence, 300 ripe fruits subjected to 5 treatments were stored at ambient temperature or at 8°C. The treatments consisted of a control, mechanical tying of the fruits, storage in moist sawdust, packing in loose sealed LDPE [low density polyethylene], and shrinkwrapping in a double layer of LDPE. Shrinkwrapping gave the best results at both temperatures. At ambient temperature, shrinkwrapping prolonged the shelf-life of fruits up to 15 days and percentage dehiscence was low. At 8°, shrinkwrapping prolonged the shelf life to 8 weeks; at this stage 20% of fruits had dehisced. Shrinkwrapping also reduced moisture loss during storage and reduced the release of the characteristic strong durian odour.